Navigating the landscape of diversity leadership: Experiences of Finnish comprehensive school principals in the Helsinki area - Jantunen, Anita; Sormunen, Kati; Loukomies, Anni; Kallioniemi, Arto; Ahtiainen, Raisa (Frontiers in Education, 2025)
This study explores the landscape of diversity leadership in Finnish comprehensive schools through the experiences and reflections of principals in the Helsinki area. Employing qualitative thematic analysis of principal interviews, we identified five key categories capturing the challenges and complexities principals navigate in leading diverse school communities: supporting structures for diversity, practical arrangements in school management, social encounters in schools, managemental issues concerning teachers and staff, and principals’ self-reflection. Principals emphasized the importance of establishing clear structures and practices to support diversity and inclusion, while also recognizing the need for flexibility and adaptability to meet the varied needs of diverse learners. They had to deal with practical challenges in managing certain aspect of diversity, constraints of municipal policies and resources, and the complexities of building positive relationships among diverse communities. Principals also engaged in critical self-reflection on their own identities, assumptions, and leadership practices in relation to diversity. Findings underscore the multifaceted nature of diversity leadership, encompassing structural, practical, social, professional, and personal dimensions. The study highlights the need for more systemic support, contextualized approaches, and professional development to build capacity for effective diversity leadership in increasingly diverse Finnish schools.